2019
DOI: 10.1186/s13636-019-0154-z
|View full text |Cite
|
Sign up to set email alerts
|

Latent class model with application to speaker diarization

Abstract: In this paper, we apply a latent class model (LCM) to the task of speaker diarization. LCM is similar to Patrick Kenny's variational Bayes (VB) method in that it uses soft information and avoids premature hard decisions in its iterations. In contrast to the VB method, which is based on a generative model, LCM provides a framework allowing both generative and discriminative models. The discriminative property is realized through the use of i-vector (Ivec), probabilistic linear discriminative analysis (PLDA), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…He et al 23 suggested a latent class model (LCM) for speaker diarization. The LCM system utilizes soft details and prevents premature difficult decisions in its isolations, was similar to the variational Bayes (VB) system of Patrick Kenny.…”
Section: Related Work: a Brief Reviewmentioning
confidence: 99%
“…He et al 23 suggested a latent class model (LCM) for speaker diarization. The LCM system utilizes soft details and prevents premature difficult decisions in its isolations, was similar to the variational Bayes (VB) system of Patrick Kenny.…”
Section: Related Work: a Brief Reviewmentioning
confidence: 99%